FASILITAS COFFEE CORNER PADA PERPUSTAKAAN UNIVERSITAS BINA DARMA PALEMBANG - Rohmaniyah Rohmaniyah; Eka Wulandari (PHENOMENON : Multidisciplinary Journal Of Sciences and Research, 2024)
The library is a place where a lot of information and knowledge is collected. Inside the library there are also several facilities to support the course of operations carried out as well as the attraction of the library itself so that users come to visit. The purpose of this study is to provide insight into one of the facilities in the library that can attract the attention of users. The method used in this research is qualitative. Data collection was carried out by visiting the Bina Darma Palembang University library and conducting research at one of the facilities provided by the library, namely coffee corner. The results obtained are that the coffee corner facility in the Bina Darma University Palembang library is not appreciated by users because there is no information or display static that explain whether the facility is for the public or only for librarians. This is due to the limited paper cups provided beside the dispenser. Even though it is located close to the user’s reading table, the user feels hesistant to use this facility.